Developing Augmented Reality-Based Flashcards to Enhance Science Literacy in Elementary Schools - Angga Setiawan; Indah Yunitasari; Diyanti Jati Pratiwi; Yesita Inka Dela; Wahyu Agung Jatmiko (FKIP UNIVERSITAS PAKUAN, 2025)
One of the basic skills that elementary school students must have is science literacy. However, the educational attainment of primary school students in a rural location remains unfulfilled. This study aims to develop flashcard-based learning media equipped with Augmented Reality (AR) technology to improve elementary school students' science literacy. The research method used is Research and Development with the ADDIE development model. Data collection methods used questionnaires and tests, while the instruments used were validation questionnaires and pre- and post-tests. Data analysis in this study used the N-Gain test. The validation results from experts indicate that the AR-based flashcard learning media is considered fasible to be implemented in the classroom for cultivate students’ science literacy. Before conducting the hypothesis test, a prerequisite test was conducted, showing the data is normally distributed, as well as a homogeneity variance. The results of the N-Gain test showed a value that indicating an improvement of students' science literacy after using this learning media. Based on the research results, it can be concluded that flashcard-based learning media with Augmented Reality technology is effective in improving the science literacy of elementary school students.